A responsabilidade tributária das empresas pertencentes ao mesmo grupo econômico e suas limitações nos planos constitucional e infraconstitucional - Lima Neto, José Gomes de (2018)
The analysis of tax liability among companies within the same economic group is this paper’s main objective. In order to do so, it was necessary to analyze the autonomy of the legal entity as a legal principle rooted on the Federal Constitution itself. Based upon this premise, the disregard doctrine was studied, focusing on its characteristics and mentions in national material laws, especially article 50 of the Brazilian Civil Code, which is anchored on the so-called “Greater Theory”. Subsequently, comments are weaved regarding unilateral rights, approaching lapsing and prescription, thus defining the legal nature of the right to require the piercing of the corporate veil, as well as its term. The study of taxpayers was also approached as a matter of constitutional content, developing into an analysis of the general theory of tax liability and the constitutional principles that underlie it, such as: legality, contributive capacity, practicability and the due legal process. Furthermore, the procedural aspects of piercing the corporate veil and its natural consequences in tax execution processes are dealt with, which basically is to redirect the debt from the original debtor to the taxpayer, defending the total enforceability of the Piercing The Corporate Veil Incident from the Brazilian Code of Civil Procedure/2015 to Tax Foreclosure Law. In order to do so, case laws were emphasized, also quoting the IRDR from the Federal Regional Court and Ruling PGFN nº 948/2017. Finally, we approach tax liability of companies belonging to the same economic group, highlighting the hierarchy of the Civil Code’s General Tax Laws, as well as the lack of specific norms for the aforementioned liability in the National Tax Code and ordinary legislation, thus establishing its constitutional and infra-constitutional limits